2020
DOI: 10.3390/molecules25215183
|View full text |Cite
|
Sign up to set email alerts
|

Effective Removal of Cyanide and Heavy Metals from an Industrial Electroplating Stream Using Calcium Alginate Hydrogels

Abstract: A real electroplating wastewater, containing 51,190 mg/L of free cyanide (CNf), 4899 mg/L of Ni and 1904 mg/L of Cu, was treated with calcium alginate hydrogel beads (CAB), pure or impregnated with biodegraded grape marc (EBGM) or activated carbon (EAC) in order to reduce the elevated load of toxic pollutants below the regulatory limits. It was evaluated the effect of increasing the amount of bioadsorbent as well as the influence of two successive adsorption cycles in the removal efficiency of pollutants. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The two electroplating wastes used in a previous work [3] contained undefined amounts of Cu or Ag. Another one contained about 30 mM Cu, 83 mM Ni and 0.9 mM Zn [37]. The fCN concentrations in these effluents can be extremely high (approximately 0.5-2 M) [2,3,37].…”
Section: Enzyme Performance In the Presence Of Heavy Metal Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two electroplating wastes used in a previous work [3] contained undefined amounts of Cu or Ag. Another one contained about 30 mM Cu, 83 mM Ni and 0.9 mM Zn [37]. The fCN concentrations in these effluents can be extremely high (approximately 0.5-2 M) [2,3,37].…”
Section: Enzyme Performance In the Presence Of Heavy Metal Saltsmentioning
confidence: 99%
“…Another one contained about 30 mM Cu, 83 mM Ni and 0.9 mM Zn [37]. The fCN concentrations in these effluents can be extremely high (approximately 0.5-2 M) [2,3,37]. The CynD was not sufficiently effective in the original gold-mine effluent (528 mM fCN) and only removed 43% of the fCN [2].…”
Section: Enzyme Performance In the Presence Of Heavy Metal Saltsmentioning
confidence: 99%
“…For instance, Perez-Ameneiro et al evaluated the use of a biopolymer based on grape marc entrapped in calcium alginate beads for the removal of pigments from an agro-industrial effluent [30] or dye compounds from winery wastewater [35] as well as to remove micronutrients from winery effluents in order to avoid eutrophication [36]. Additionally, an alginate-based polymer with grape marc has also been tested as an eco-adsorbent for removal of copper (II) from aqueous streams [37]; for adsorption of binary mixtures of dyes [38]; and for the removal of cyanide and transition metals from industrial electroplating process waters [39]. Nevertheless, it should be high-lighted that this type of biopolymer has never been tested to recover biosurfactants present in corn steep water.…”
Section: Calcium Alginate-based Biopolymers Performance In Liquid-solid Process To Recove Biosurfactants From Corn Steep Watermentioning
confidence: 99%
“…However, the biopolymer capacities for metal ions were higher. Pérez-Cid et al [39] concluded that calcium alginate hydrogel beads can be considered a bioadsorbent with a high capacity to remove free cyanide (1177 mg/g) and transition metals (Ni, Cu and Zn as follows 107.3, 39.5 and 1.52 mg/g, respectively) in electroplating streams. In this case, the introduction of composted grape marc in the calcium alginate bead formulation did not produce significant improvements in the adsorption capacity.…”
Section: Calcium Alginate-based Biopolymers Performance In Liquid-solid Process To Recove Biosurfactants From Corn Steep Watermentioning
confidence: 99%
“…Cyanide (−CN) plays a variety of roles in the water environment, such as a source for nitrogen and carbon, a reducing and complexing agent, a pseudohalogen, and a toxic compound among others, owing to its high hydrophilicity, low redox potential, and strong electron-withdrawing ability. , Cyanide is widely found in industrial wastewaters with different concentrations, e.g., those from metal surface treatment (45–300 mg/L), noble metal ore dressing (50–500 mg/L), petroleum refining and coking (10–1000 mg/L), and other industrial production (somewhere between 10–4000 mg/L) (Table S1). ,, Cyanide-containing coking wastewater with high organic matter contents, high toxicity, and high ammonia nitrogen concentrations is discharged at a rate of 270 million m 3 /year in PR China .…”
Section: Introductionmentioning
confidence: 99%